2017
DOI: 10.3329/bmj.v45i3.33123
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of intrauterine fetal death in Dhaka National Medical College Hospital

Abstract: Intrauterine fetal death (IUFD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…We believe this aspect is also important to give a just and dutiful answer to the couple that suffered this dramatic event, which in our population occurred after 30 weeks of gestation in 72% of the cases, when the chances of newborn survival increase significantly with good intensive care, and after 36 weeks in 34% of cases, meaning at term. Some 88% of IUFD cases recorded in this study occurred in the antepartum period and this figure is in line with what was reported by other works carried out in high-income countries, where 90% of deaths in utero occur precisely in this period and are often associated with preventable risk factors, such as obesity, smoking, failure to identify pregnancies at risk [6,[27][28][29][30][31][32][33][34][35]. Therefore, being able to understand the cause of death in utero would allow addressing the available resources more appropriately to combat the etiological factors on which it is possible to implement concrete prevention.…”
Section: Discussionsupporting
confidence: 91%
“…We believe this aspect is also important to give a just and dutiful answer to the couple that suffered this dramatic event, which in our population occurred after 30 weeks of gestation in 72% of the cases, when the chances of newborn survival increase significantly with good intensive care, and after 36 weeks in 34% of cases, meaning at term. Some 88% of IUFD cases recorded in this study occurred in the antepartum period and this figure is in line with what was reported by other works carried out in high-income countries, where 90% of deaths in utero occur precisely in this period and are often associated with preventable risk factors, such as obesity, smoking, failure to identify pregnancies at risk [6,[27][28][29][30][31][32][33][34][35]. Therefore, being able to understand the cause of death in utero would allow addressing the available resources more appropriately to combat the etiological factors on which it is possible to implement concrete prevention.…”
Section: Discussionsupporting
confidence: 91%
“…6,8 The occurrence of prenatal loss was 26 per 1000 livebirths in a study in Bangladesh. 15 In present study the occurrence of fetal demise was high . The reason may be our institute is a tertiary care referral centre.…”
Section: Discussionsupporting
confidence: 40%
“…Patel S et al, Anjali C et al and Bakshi L et al had reported IUFD due to congenital malformations in 2.5%, 10.5% and 8.3% respectively. 4,7,12 IUFD occurred due to APH in 29(15.0%). Out of these abruption and placenta previa were present in 15(7.7%) and 14(7.2%) respectively.…”
Section: Resultsmentioning
confidence: 99%